Natural 5-Aminolevulinic Acid: Sources, Biosynthesis, Detection and Applications - Jiang, Meiru; Hong, Kunqiang; Mao, Yufeng; Ma, Hongwu; Chen, Tao; Wang, Zhiwen (Frontiers in Bioengineering and Biotechnology, 2022)
5-Aminolevulinic acid (5-ALA) is the key precursor for the biosynthesis of tetrapyrrole compounds and has wide applications in medicine, agriculture and other burgeoning fields. Because of its potential applications and disadvantages of chemical synthesis, alternative biotechnological methods have drawn increasing attention. In this review, the recent progress in biosynthetic pathways and regulatory mechanisms of 5-ALA in biological hosts are summarized. The research progress on 5-ALA biosynthesis via the C4/C5 pathway in microbial cells is emphasized, and the corresponding biotechnological design strategies are highlighted and discussed in detail. In addition, the detection methods and applications of 5-ALA are also reviewed. Finally, perspectives on potential strategies for improving the biosynthesis of 5-ALA and understanding the related mechanisms to further promote its industrial application are conceived and proposed.